Molecular Mechanisms Involved in Mesenchymal Stem Cell Migration to the Site of Acute Myocardial Infarction. (22nd June 2009) - Kollar, Katarina; Cook, Matthew M.; Atkinson, Kerry; Brooke, Gary
Abstract : Mesenchymal stem cells or multipotent mesenchymal stromal cells (both referred to as MSC) have been shown in some studies to have a beneficial effect on myocardial recovery after infarct. Current strategies for MSC delivery to heart involve intravenous, intraarterial, and intramuscular delivery. Different routes of MSC delivery and a lack of knowledge of the mechanisms that MSC utilise to migrate in vivo has most likely led to the marked variations in results that have been found. This review aims to summarise the current knowledge of MSC migratory mechanisms and looks to future methods of MSC manipulation prior to delivery in order to enhance MSC migration and engraftment.